PENGARUH KEBIJAKAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Muhammad Istan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aimed to test whether the company’s performance mediated thecompany policy in influencing the value of the firm. The study took a sample of 116manufacturing companies listed in Indonesia Stock Exchange period of 2004 until2006, with purposive sampling method. The theory underlying this research istheory of capital structure (Modigliani and Miller, 1963), and agency theory(Jensen and Meckling, 1976). Results of this research show that financial leveragesignificant negative effect on company’s performance, and a significant positiveinfluence firm value. Capital expenditure is not significant negative effect on thecompany’s performance and firm value. While the manager incentives has asignificant positive on company’s performance, but no significant effect on firmvalue. Specific findings of this research is that the company’s performancemediates the influence of corporate managers incentives to firm value.